1982
DOI: 10.1258/002367782780908751
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analyses of the vertebral anomalies of the IS strain of rat and the development of a BN congenic line with the anomalies

Abstract: SummaryIt is suggested that the anomalies in the IS rat are controlled by one or several genic factor(s) unrelated to LG I, II, IV, V, and VI and the LGs containing Amy-l and Cs-lloci.In the IS strain of rat (Rattus norvegicus), almost all individuals express singly or jointly several vertebral anomalies, mainly of the lumbar vertebrae. The anomalies include complete and incomplete unsegmentation, wedged and butterfly vertebrae, and result in scoliosis, kyphosis or both in about 50% of the rats. So, the IS str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…Since in this study, we did not separated the plasma ALPs into bone, liver and intestinal ALPs, and also we did not measure phosphoethanolamine in the urine that is one of the diag-nostic findings of human hypophosphatasia [8], it is not certain whether the low plasma ALP activities in the IS rats are homologous with those in human hypophosphatasia or not. Now, we are developing a BN congenic line with the IS strain's vertebral anomalies [19]. By comparing the ALP activities of rats with and without vertebral anomalies in the congenic line, the relations between low ALP activity and vertebral anomaly will be clearly confirmed.…”
Section: Discussionmentioning
confidence: 97%
“…Since in this study, we did not separated the plasma ALPs into bone, liver and intestinal ALPs, and also we did not measure phosphoethanolamine in the urine that is one of the diag-nostic findings of human hypophosphatasia [8], it is not certain whether the low plasma ALP activities in the IS rats are homologous with those in human hypophosphatasia or not. Now, we are developing a BN congenic line with the IS strain's vertebral anomalies [19]. By comparing the ALP activities of rats with and without vertebral anomalies in the congenic line, the relations between low ALP activity and vertebral anomaly will be clearly confirmed.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the ISR model has similarities to HVF mice in having kyphosis, that is associated with segmentation defects affecting mainly the lumbar area, as well as narrowing of intervertebral spaces, irregularity of adjacent ends of vertebral bodies, and wedging and complete bony fusion of adjacent vertebral bodies 48, 49. However, the ISR model is suggested to have an autosomal recessive inheritance50 and although reduced expression of Hox10 and Hox11 have been reported,49 a mutation has not yet been identified. Details of body weight, lean mass, fat mass, and BMD content were not reported in the ISR model 48.…”
Section: Discussionmentioning
confidence: 99%
“…Yamada et al (1982) suggested that the causal gene was a single autosomal recessive one with a penetrance of 50%. Clinico-biological studies disclosed a low level of serum alkaline phosphatase activity in ISR but this appeared unrelated to spinal malformations , Takahashi et al 1981.…”
Section: Discussionmentioning
confidence: 99%